Pelatihan Pengembangan Media Pembelajaran Interaktif Berbasis Kearifan Lokal Malaka untuk Meningkatkan Prestasi Belajar Siswa - Daud Dakabesi (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
Learning media has a very important role in learning activities because it is an intermediary tool that can help teachers in delivering lesson materials as well as formative and summative evaluations to students. This community service activity aims to train teachers' skills in developing interactive learning media based on local wisdom in improving student learning achievement. This activity was carried out in Malaka Regency, precisely at Sinar Pancasila Betun Private High School on June 11 and 12, 2025, involving teachers at the school, Sinar Pancasila Betun Private Middle School teachers and some chemistry teachers from schools in Malaka Regency. The method used in this community service activity is Participatory Action Research (PAR), which in the process of finding problems or obstacles that occur at partner locations, then looking for the strengths of each teacher to be drilled and developed to solve problems experienced by teachers. The results of this activity show that teachers can independently develop and produce interactive learning media, namely Lumio by Smart, by integrating local Malaka culture into the material they teach. Furthermore, the developed media also addresses teachers' concerns regarding the lack of laptops, as this interactive learning media can be created using the mobile phones each teacher owns. All teachers who participated in the training were enthusiastic about creating and producing learning media and were willing to implement the resulting media in their learning activities. They expressed their hope that it would increase student motivation, which would ultimately lead to positive improvements in student achievement.